PERLINDUNGAN HUKUM TERHADAP KONSUMEN YANG MENGALAMI KERUGIAN AKIBAT PENGIRIMAN BARANG OLEH PERUSAHAAN EKSPEDISI LAUT MENURUT UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Roida Nababan; Martono Anggusti; Sonya Lorensa Sirait (Magister Hukum Universitas HKBP Nommensen, 2021)
The responsibility of the shipping company in reimbursing losses suffered by consumers in the delivery of goods resulting from damage to goods or loss of goods then looking for evidence that damage and loss of goods occur due to transportation of goods to the detriment of the consumer in accordance with Article 188 of Law No. 22 of 2009 concerning Road Traffic and Transportation and Article 1 number 1 of Law No.8 of 1999 concerning Consumer Protection. From the results of the study it can be concluded that first, if the goods transported are lost / stolen or damaged due to the fault of the transporting company, then he must be responsible. Second, the legal efforts undertaken by the consumer, namely the resolution of disputes outside the court, the peaceful settlement of disputes by the parties to the dispute is a legal remedy that was first attempted by the parties to the dispute, before the parties chose to settle the dispute through the Consumer Dispute Settlement Agency. The results of the study the authors provide advice to protect consumers, shipping companies responsible for compensation for goods / or services must be replaced with the actual price of goods in accordance with the law by looking at a written contract that is agreed between the business actor and the consumer.